Pemanfaatan Kahoot Untuk Pembelajaran Matematika Siswa Kelas X Pada Materi Sistem Persamaan Linear Dua Variabel - Sartika Sartika; Mira Octafianti (Journal on Education, 2019)
Mathematics education at this time there are still many who have not developed because of the many paradigms that think that mathematics is a science that uses abstract concepts. There are still many learning mathematics in schools that use ordinary learning so that there is no creativity or something that can arouse students' creativity and activity in this class, making researchers test the effectiveness of learning mathematics by utilizing technology in class X SMK TI Garuda Nusantara Cimahi. In this study the type of research used is research methods and development (Research and Development). Research and Development is a type of research method that uses needs analysis research to produce certain products, also used to test the effectiveness of these products so that they can function in the wider community. The results of the assessment were obtained on a written test of 40.4% and tests using the 59.6% kahoot application. So based on the criteria by calculating the average and the percentage of success of the students obtained written test of 40.4% with the criteria "Not interesting" and the test using the kahoot application of 59.6% with the criteria "Interesting". This shows that the evaluation tool using the kahoot application is feasible to be used to improve mathematics learning.